Glucocorticoids may compromise the effect of gefitinib in non-small cell lung cancer - Wang, Hsian-Yu; Chang, Yu-Ling; Cheng, Chun-Chun; Chao, Min-Wu; Lin, Su-I; Pan, Shiow-Lin; Hsu, Chih-Cheng; Liu, Tsang-Wu; Cheng, Han-Chin; Tseng, Ching-Ping; Liu, Shih-Jen; Tsai, Hui-Ju; et al. (My University, 2016)
The epidermal growth factor receptor (EGFR)-targeting tyrosine kinase inhibitors (TKIs) have shown remarkable benefits in non-small cell lung cancer (NSCLC) patients with drug-sensitive mutations in the EGFR gene. Responsive patients are usually continuously prescribed with TKIs until disease progression. Glucocorticoids (GCs) are potent homeostasis maintaining drugs and are frequently used in cancer patients to alleviate discomforts caused by anti-cancer therapies. Several previous studies reported that concomitant use of GCs may compromise the efficacy of chemo-therapeutics in patients with solid tumors. Little is known in the concomitant use of target therapy with GCs in treating NSCLC. In this study, we hypothesized that concomitant use of GCs in EGFR-TKI therapy may be detrimental and addressed this issue using cell cultures and xenograft studies followed by a retrospective population study based on data from the Taiwan national health insurance system. In cell cultures and xenograft studies, GCs were shown to unequally compromise the anti-cancer efficacy of TKIs in both PC9 and NCI-H1975 NSCLC cells models. In the retrospective population study, patients with similar disease status that were co-medicated with GCs had a significantly higher risk of disease progression.
Keywords: NSCLC; EGFR; TKI; glucocorticoids; national health insurance research database taiwan